2008
DOI: 10.1021/jm800800c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure−Activity Relationship Studies of Highly Potent Novel Oxazolidinone Antibacterials

Abstract: Novel antibacterial biaryl oxazolidinones bearing an aza-, an oxa-, or a thiabicyclo[3.1.0]hex-6-yl ring system were synthesized, and their in vitro antibacterial activity and structure-activity relationships (SAR) were evaluated. Most of the synthesized biaryl bicyclo[3.1.0]hex-6-yl oxazolidinones showed good antibacterial activity against the Gram-positive and -negative bacteria tested. Regarding SAR trends among the C-ring subtypes, the pyridyl ring was preferable to the phenyl ring. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(32 citation statements)
references
References 22 publications
0
32
0
Order By: Relevance
“…As such, this group has been retained in oxazolidinones, having undergone significant development efforts (eperezolid, RWJ-416457, and radezolid). Although many other heterocyclic substitutions were poorly tolerated (58), certain analogs, such as the 1,2,3-triazoles from AstraZeneca ("compound 2" [57] and "example 1" [24]) and Kyorin/Merck (AM-7359) (37,52) showed good activity, possibly due to different binding modes in the ribosome (57). Thus, in addition to the 1,2,3-triazole, there is now significant interest in other A-ring C-5 substituents, such as the hydroxymethyl (torezolid) group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, this group has been retained in oxazolidinones, having undergone significant development efforts (eperezolid, RWJ-416457, and radezolid). Although many other heterocyclic substitutions were poorly tolerated (58), certain analogs, such as the 1,2,3-triazoles from AstraZeneca ("compound 2" [57] and "example 1" [24]) and Kyorin/Merck (AM-7359) (37,52) showed good activity, possibly due to different binding modes in the ribosome (57). Thus, in addition to the 1,2,3-triazole, there is now significant interest in other A-ring C-5 substituents, such as the hydroxymethyl (torezolid) group.…”
Section: Discussionmentioning
confidence: 99%
“…Later studies demonstrated that substituents in the 4 position of the 3-phenyloxazolidinone can enhance antibacterial potency, especially those containing a 3-aryl or heteroaryl ring (6,31). Some of the most potent compounds are the 3-biphenyloxazolidinones discovered by Rib-X (RX-1741, formerly known as Rx-01_667) (64,78,79), the 3-(4-pyrid-3-yl)-phenyloxazolidinones discovered by Dong-A (DA-7867) (77), Kyorin/Merck (AM-7359) (37,52), and AstraZeneca ("compound 13") (56), and the 3-(azolylphenyl)-oxazolidinones from Pharmacia & Upjohn ("compound 4") (20) (Fig. 1).…”
mentioning
confidence: 99%
“…Novel antibacterial biaryl oxazolidinones that bear an aza-, an oxa-, or a thiabicycloA C H T U N G T R E N N U N G [3.1.0]hex-6-yl ring systems were synthesized by Komine et al [114] Most of the synthesized biaryl bicycloA C H T U N G T R E N N U N G [3.1.0]hex-6-yl oxazolidinones showed good antibacterial activity against Gram-positive and Gramnegative bacteria.…”
Section: Antifungal and Antibacterialsmentioning
confidence: 99%
“…[1] Misusing of antibiotics has been observed for many years, leading to an increased antibiotic resistance of bacterial pathogens in hospitals and communities, both in gram-negative and gram-positive bacteria. [2][3][4][5] Therefore, significant efforts have been made by many scientists to improve the efficacy and antimicrobial spectrum of existing drugs. [6][7][8] At present, the most commonly used antimicrobial reagents mainly include four broad categories [9][10][11] : (i) the oxidants, such as peroxides; (ii) the electrophilic agents, such as copper and mercury; (iii) organic biocides, such as formaldehyde; and (iv) cationic active biocides, such as chlorhexidine and quaternary ammonium compounds.…”
Section: Introductionmentioning
confidence: 99%